2013
DOI: 10.1007/s12020-013-9912-3
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of combining serum uric acid and high-sensitivity C-reactive protein for risk stratification of patients with metabolic syndrome in community-dwelling women

Abstract: Metabolic syndrome (MetS) is associated with an increased risk of major cardiovascular events. In women, increased uric acid (UA) levels are associated with MetS and its components. High-sensitivity C-reactive protein (hsCRP) levels are also associated with MetS, and hsCRP levels could be modulated by UA. We investigated whether combining UA and hsCRP levels are independently associated with MetS and insulin resistance in Japanese community-dwelling women. From a single community, we recruited 1,097 women (63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
16
2
Order By: Relevance
“…Because the study participants were mainly healthy adults, which limits generalizability, the prevalence of MetS was very low, unlike the prevalence of MetS in the general population. In a Japanese study of community-dwelling women, the ORs of hsCRP were significantly higher for MetS (OR = 3.23) and its components after controlling for age, smoking, and alcohol consumption [17]. Our results showed a stronger association after adjusting for demographics, socioeconomic status, and general health variables than that in the previous study (OR = 4.59).…”
Section: Discussioncontrasting
confidence: 66%
“…Because the study participants were mainly healthy adults, which limits generalizability, the prevalence of MetS was very low, unlike the prevalence of MetS in the general population. In a Japanese study of community-dwelling women, the ORs of hsCRP were significantly higher for MetS (OR = 3.23) and its components after controlling for age, smoking, and alcohol consumption [17]. Our results showed a stronger association after adjusting for demographics, socioeconomic status, and general health variables than that in the previous study (OR = 4.59).…”
Section: Discussioncontrasting
confidence: 66%
“…In addition to significant renal effects, excess accumulation of SUA can lead to various diseases . Recent epidemiological, experimental, and clinical studies have consistently showed that SUA has an important causative role in the onset and progression of hypertension, diabetes, metabolic syndrome, CVD, and CVD mortality . Moreover, a change in SUA level may be related to other lifestyle‐related factors, such as alcohol consumption, smoking status, socioeconomic stress, and exercise habits .…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Korea including ~2400 individuals, high levels of UA (>6.5 mg/dL in men and >5.1 mg/dL in women) were associated with a more than two-fold probability of MetS (20) independently of sex. This study was observational and cross-sectional and no adjustment was made for prevalent diabetes mellitus and body composition.…”
Section: Discussionmentioning
confidence: 99%